Application of oat flour in rye-wheat bread production technologies - Zh. M. Kunasheva; M. H. Kodzokova (Новые технологии)
In the modern world the food industry faces the main task of providing the population with high-quality food. The use of non-traditional types of raw materials in order to enrich the category of everyday products will contribute to solving this problem. The development of recipes and the introduction of new types of bakery products into production will contribute not only to expanding the range, but also to providing the population with a healthy diet. The presence of bakery products in relatively large volumes can be noted in the diets of different categories of the population. The main component of a healthy nutrition policy in the field of PPRS production is the development of new recipes and improved technologies for food products enriched with safe non-traditional raw materials that are carriers of essential nutrients. These issues are relevant for the improvement of all categories of the population. At the same time, the quality indicators of finished bakery products must comply with existing requirements.The object of the research is the recipe for rye-wheat bread with the use of oat flour. An important activity of the bakery industry can be identified as the use of non-traditional raw materials in unified recipes for finished products, which contributes to the expansion of the bakery market. One of the most important tasks solved by the baking industry is the inclusion of high-quality and safe products of everyday use in the diet of different categories of the population. The solution of the task will be facilitated by the use of promising types of raw materials, characterized by a variety of chemical composition and favorable technological properties.The purpose of the research is the use of non-traditional raw materials in the form of oat flour to develop a recipe and technology for the production of rye-wheat bread with improved properties and quality indicators.The main aspect of the research work is to determine the effect of oatmeal on the quality indicators of semi-finished products based on thick rye sourdough, the study of the organoleptic properties of products, and the choice of dosages of oatmeal. The degree of influence of different amounts of oatmeal on the physicochemical parameters of rye-wheat bread has been revealed, and the shelf life of product samples using oatmeal established in the course of the research.